Analysis of the Impact of YouTube and TikTok Addiction on Early Childhood: A Literature Review - Cynthia, Ade; Munisa, Munisa (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the impact of addiction to YouTube and TikTok platforms on early childhood. Using a qualitative literature review method, this research examines various literature related to the influence of social media on children’s cognitive, social-emotional, and psychological development. The results show that unsupervised usage may lead to vocabulary decline, disrupted social interaction, sleep disorders, and behavioral problems. On the other hand, when used with parental guidance, these platforms also have the potential to enhance children’s creativity, language comprehension, and curiosity. Data from APJII and Common Sense Media indicate high internet usage among early childhood children in Indonesia. Therefore, active parental involvement in regulating the duration and content accessed by children is crucial to avoid negative impacts and optimize the educational potential of these media.